Mitochondrially-imported cytoplasmic tRNA(Lys)(CUU) of Saccharomyces cerevisiae: in vivo and in vitro targetting systems. - Tarassov, I A (1992)
The cytoplasmic tRNA(Lys)(CUU) (tRNA(1Lys)) is the single yeast tRNA species to be traffiked from the cytoplasm into the mitochondrial compartment of the cell. To study mechanisms of this targetting we worked out two test systems. The in vivo system based on the electroporation of intact yeast cells was used to introduce labelled tRNAs into the cytoplasm. All tRNA species tested were effectively introduced into the cytoplasm, but only the cytoplasmic tRNA(1Lys) was found in the mitochondrial compartment within 1-2 hours after the electroporation procedure. The in vitro system permits specific transfer of the tRNA(1Lys) into isolated mitochondria. Contrary to the known systems for protein transport into isolated mitochondria, mitochondrial import of tRNA(1Lys) in vitro requires the presence of soluble cellular proteins in the reaction mixture. The translocation proved to be ATP-dependent and to require the presence of an ATP-generation system in the reaction. Preincubation of the tRNA with the total cellular extract of the cell markedly increases the rate of the translocation. Two protein fractions are necessary to direct the import in vitro. The first one has high heparin-binding affinity, while the other protein fraction is not retained by heparin-Sepharose.